Hungarian Monitoring, 9 March 1989 . [Magyar rádiófigyelő], 1989. március 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Demonstration held at the end of February in the capital of Soviet Moldavia - International reactions to the Vienna conference - Soviet academics on the "Satanic Verses" - On the trust-building Vienna conference - Red-Green coalition in West Berlin - Prague disputes Radio Free Europe report on Husak's serious health problems Domestic Affairs: - Parliament in session: debate on the new constitution - Representative Imre Varga proposes investigating Warsaw Pact agreement additional clauses - News and denial of halt to Gabčíkovo-Nagymaros construction works - Iván T. Berend: historical committee's report essentially means the rehabilitation of Imre Nagy, calls intervention in Czechoslovakia in 1968 a mistake Economy: - Restructuring the Lab Technology Works Külpolitika: - Tüntetés volt február végén Szovjet Moldávia fővárosában - Külföldi reagálások a bécsi konferenciáról - Szovjet tudósok a Sátáni versek-ügyről - A bécsi bizalomerősítő tanácskozásokról - A nyugat - Berlini vörös-zöld koalícióról - Prágában cáfolják a SZER jelentését Husak súlyos betegségéről Belpolitika: - Országgyűlési ülésnap: vita az új alkotmányról - Varga Imre képviselő a VSZ záradékainak felülvizsgálását javasolta - A bős-nagymarosi építkezés leállításának híre - És cáfolata - Berend T. Iván: a történelmi bizottság beszámolója lényegében Nagy Imre rehabilitálását jelenti. - A 68-as csehszlovákiai beavatkozást hibás lépésnek nevezte Gazdaság: - Szanálják a Labor Műszeripari Műveket